Profitability, Liquidity, Board Size, and Gender Diversity: Their Impact on Financial Distress - Darojatuz Zakiyyah Maisarotus Sa'diyah; Wikan Isthika; Hermawan Triono; Melati Oktafiyani (Penerbit Goodwood, 2025)
Purpose: This study intends how to examine profitability, liquidity, board size, and gender diversity affect to financial distress in consumer cyclicals companies listed on the Indonesia Stock Exchange between 2021 and 2023. Methodology/approach: This study applied a quantitative method with purposive sampling, using 137 samples collected from annual reports and official websites then used a data from a company with indicators of potential bankruptcy. Data analysis was conducted using IBM SPSS 26, including descriptive statistics, classical assumption tests, multiple linear regression, and using hypothesis testing. Results/findings: The study produce profitability has a positive and significant affect. Liquidity, board size, and gender diversity their not significantly affect to financial distress. Conclutions: High profitability is lead to a lower risk of financial distress in company. Liquidity ratio, board size, and then gender diversity composition variables not directly influence distress risk. Limitations: This study found that only one independent variable, namely profitability, has a positive significant influence on financial distress. Contribution: The study contributes to corporate to financial management and can guide investors, policymakers, and company managers in identifying early signs of financial distress through internal financial indicators.